Underdeveloping Nigeria through reregulation: Will community banks survive? - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 1994)
Regulating the financial system through restrictions on foreign exchange, interest rate controls and constraints imposed on financial institutions have been among the principal instruments of financial repression in low-income countries. In recent years, many have taken to deregulation, but mostly in response to donor persuasion and pressure rather than conviction. Unpopular political regimes have found it difficult to get over their initial hardship period which the restructuring of a whole economy and its financial system entails. The Nigerian Government, in a populist gesture, has just succumbed to the temptations of re-regulation. Commercial banks are hard hit. Small farmers and microentrepreneurs are among the first victims
Keywords: 330